School Education According to Indian National Education Policy 2020 – A Case Study - PALLATHADKA, HARIKUMAR; MANOHARMAYUM, DOLPRIYA DEVI; PALLATHADKA, LAXMI KIRANA; MAKKI, VASISTA RAMA RANJAN (The journal of contemporary issues in business and government, 2021)
In India, from the beginning, education is not considered as an investment. Education’s role is of utmost importance in today’s world as it leads to the overall development of an individual. As education provides human resources that lead to economic development, it is now a practical reality that much has to be done to uplift this sector towards new horizons of change. The Government tries to give importance to the educational sector, but this sector’s allotment is comparatively less. After India’s independence, the Government of India came up with various educational policies that give importance to the Universalization of education, raising the literacy level through the implementation of various programs, which is a great job. In recent times, the Government’s new policy, i.e., National Education Policy 2020, has aimed to bring changes in the education field. In this article, school education reforms are given prominence, and 30 respondents are considered for the study.